Carbide and DLC synthesis within the Ti-Al-C system via sputter deposition - Viloan, Rommel Paulo Basence (Materials Science and Engineering Program, College of Science, University of the Philippines Diliman, 2013)
Ti-Al-C thin films were synthesized by sputter deposition using a magnetized Sheet Plasma Negative Ion Source (SPNIS). Several factors affecting the deposition were considered in this study: methane percentage, deposition time, filling pressure, target bias and deposition set-up. The relative composition of the thin films was determined by energy-dipersive x-ray spectroscopy (EDX). X-ray diffraction (XRD) spectra of selected thin films indicated the formation of binary (TiC) and ternary carbides (Ti3AlC and Ti3AlC2) within the Ti-Al-C system. Surface morphology was investigated using atomic force microscopy (AFM) and it was found that the root mean square of roughness (Rrms)for most of the films were less than the Rrms of the substrate which indicated smaller surface morphology. Almost all of the samples were found to exhibit hydrophobicity and most were found to exhibit higher contact angles when compared to the stainless steel substrate. The raman spectra of the films indicated DLC formation especially for hydrgenated samples synthesized with high methane percentage and high pressure environment. Hydrogen-free DLC was also synthesized by using a moderate target bias and relatively short deposition time and was found to have the lowest ID/IG ratio in this study.